in vitro drug combination measurements predict treatment outcomes in mouse models of Mycobacterium tuberculosis infections - LARKINS-FORD, JONAH. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Bree Aldridge.; Committee: Carol Kumamoto, Andrew Camilli, Shumin Tan, and Eric Rubin.; Keyword: Microbiology.